ORGANOLEPTIC PROPERTIES OF FISH-BASED PROCESSED PRODUCTS - Marthinus I. H. Hanoatubun (Berkala Perikanan Terubuk, 2022)
One of the weakness of anchovies (Stolephorus sp). As also owned by other animal commodities is to have the water level which is quite high, have the trait of being easily perishable food if someone is the high of being scooped and die. Because business is considered important increase the power lasts long and by the permission of fishery products in after harvest covering the process of preserving and processing. One of the ways of preserving and processing anchovies that you can do is through the process of diversification. Food diversification give variety to staple food consumed, so that they do not just focus on one type of product. The purpose and benefit of this research know diversification processed product development anchovies, and to knows the organoleptic. Test of a produced. The benefi t of this research is producing a the processed products are developed the anchovies, and as a source of information for that requires. This research activity consists of two phases product processing. The first stage of production of fish anchovies and pulverized and the II production meatballs product, as a nugget of and krispydelly fish. Visibility, texture, odor to the processed products and think there a nuggetof an 73-93% compared with meatballs and krispydellyprocessed.